Metrology of pH Measurements in Brackish Waters—Part 2: Experimental Characterization of Purified meta-Cresol Purple for Spectrophotometric pHT Measurements - Müller, Jens D.; Rehder, Gregor (Frontiers in Marine Science, 2018)
Spectrophotometric pH measurements allow for an accurate quantification of acid-base equilibria in natural waters, provided that the physico-chemical properties of the indicator dye are well known. Here we present the first characterization of purified m-Cresol Purple (mCP) directly linked to a primary pH standard in the salinity range 5-20. Results were obtained from mCP absorption measurements in TRIS buffer solutions. The pHT of identical buffer solutions was previously determined by Harned cell measurements in a coordinated series of experiments. The contribution of the TRIS/HCl component to the ionic strength of the buffer solutions increases towards lower salinity: This was taken into account by extrapolating the determined pK2e2 to zero buffer concentration, thereby establishing access to a true hydrogen ion concentration scale for the first time. The results of this study were extended with previous determinations of pK2e2 at higher and lower salinity and a pK2e2 model was fitted to the combined data set. For future investigations that include measurements in the salinity range 5-20, pHT should be calculated according to this pK2e2 model, which can also be used without shortcomings for salinities 0-40 and temperatures from 278.15 – 308.15 K. It should be noted that conceptual limitations and methodical uncertainties are not yet adequately addressed for pHT determinations at very low ionic strength.